2022
DOI: 10.3389/fnint.2022.804743
|View full text |Cite
|
Sign up to set email alerts
|

Improving Imaging of the Brainstem and Cerebellum in Autistic Children: Transformation-Based High-Resolution Diffusion MRI (TiDi-Fused) in the Human Brainstem

Abstract: Diffusion-weighted magnetic resonance imaging (dMRI) of the brainstem is technically challenging, especially in young autistic children as nearby tissue-air interfaces and motion (voluntary and physiological) can lead to artifacts. This limits the availability of high-resolution images, which are desirable for improving the ability to study brainstem structures. Furthermore, inherently low signal-to-noise ratios, geometric distortions, and sensitivity to motion not related to molecular diffusion have resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 55 publications
(79 reference statements)
0
12
0
Order By: Relevance
“…This study set out to identify the relationships between sensory features and white matter microstructure of the underexplored brainstem in autistic and non-autistic children. Using a novel DWI protocol that improved the apparent resolution of the brainstem and cerebellum [93], we precisely delineated brainstem and brainstem-cerebellar white matter tracts and examined their associations with total sensory features and specific sensory responses. Consistent with our hypotheses, results revealed that the microstructural properties of brainstem white matter tracts were associated with sensory features, particularly in autistic children.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study set out to identify the relationships between sensory features and white matter microstructure of the underexplored brainstem in autistic and non-autistic children. Using a novel DWI protocol that improved the apparent resolution of the brainstem and cerebellum [93], we precisely delineated brainstem and brainstem-cerebellar white matter tracts and examined their associations with total sensory features and specific sensory responses. Consistent with our hypotheses, results revealed that the microstructural properties of brainstem white matter tracts were associated with sensory features, particularly in autistic children.…”
Section: Discussionmentioning
confidence: 99%
“…In all, the present findings, combined with theoretical work and studies implicating the brainstem in autism [18][19][20], suggest that the brainstem and cerebellum may be integral contributors to the sensory experiences of autistic individuals. Therefore, even though the imaging of the brainstem may require special acquisition and processing procedures [49], including free water elimination, EPI distortion correction, and careful consideration of brainstem masking, these steps are worth taking, as the brainstem and cerebellum are likely key areas to study to better understand the neurobiological basis of the autistic experience.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the aim of the present study was to use a brainstem‐optimized image acquisition and post‐processing methods (Guerrero‐Gonzalez et al, 2022) combined with a mapping of the autonomic/pain/emotion brainstem nuclei (Bianciardi et al, 2015, 2018; García‐Gomar et al, 2019, 2022; Singh et al, 2019, 2021) to test if microstructural properties of brainstem relate to individual variation in core social and repetitive‐behavior features in autistic children. Children with no known diagnosis of autism or other neurodevelopmental conditions (i.e., “non‐autistic” children) are included for context and for examining these associations across the broader population, but they are not included for direct group comparisons, as the autonomic literature suggests greater within‐group than between‐group variation.…”
Section: Introductionmentioning
confidence: 99%